CREATING GRADUONYMIC ROWS IN VERB SEMANTIC CATEGORIES IN UZBEK AND ENGLISH LANGUAGES - Otaboeva Mazmuna Rahimovna; Jurayeva Zulayho Shamsiddinovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article is developed to the analysis of graduonymic lines, formed on the basis of verb semantic categories of the English and Uzbek languages and the phenomenon of graduonymy in verbs.